The Impact of different levels of organic plant-based compost on the macro and micro elements, secondary metabolites and water soluble vitamins content of Moringa oleifera leaves - Ngwenya, Nkazimulo (University of the Witwatersrand, Johannesburg, 2023)
Moringa oleifera leaves are a high source of phytochemicals and nutrients inclusive of macro and micro elements, secondary metabolites and water-soluble vitamins. All the M. oleifera plant parts inclusive of its leaves have been widely utilised for nutritional and/ medicinal properties because of its high levels of minerals and phytochemicals. Studies have been conducted targeting the improvement of the quantity of M. oleifera nutrient content. However, with increased consumer awareness of high quality organic, consumer and environmentally safe products there is increased need to improve the quality of M. oleifera products. One of the major factors impacting the quality and quantity of M. oleifera leaf nutrients is cultivation practices. Particularly soil amendments applied to improve plant biomass have also been found to significantly improve nutrient content of M. oleifera leaves. However, the popularly used soil amendments which are in the form of synthetic fertilisers or animal based compost have raised environmental and product safety concerns. They contain, among other contaminants, traces of heavy metals and other toxins which are harmful to both the environment and consumers of the produce. Producers of herbal plants such as M. oleifera are looking for sustainable, environmental safe ways of improving the quantity and quality of the produce. Application of organic plant based compost was therefore investigated as a potential soil amendment source in improving M. oleifera nutrients in an organic, clean sustainable way, and thus improving the quality of the produce. The use of plant based compost to improve the nutritional content of M. oleifera grown in South Africa was reported in this thesis. The primary objective of the study was to assess the impact of the plant-based organic compost on the macro and micro elements composition, secondary metabolite accumulation and distribution and water soluble vitamins content in M. oleifera leaves. This work is novel and worth exploring as it seeks to investigate for the first time the correlation between the use of plant-based organic compost and quality improvement in terms of nutrient content of M. oleifera leaf biomass. Furthermore, this research is the first of its kind which looks at the impact of compost on the nutritional content encompassing, macro and micro nutrients, secondary metabolites and water soluble vitamins in M. oleifera grown in South Africa. In addition, the developed and validated high performance liquid chromatography (HPLC) method for the simultaneous quantification of five B vitamins was successfully used in the identification and quantification of the vitamins. Clay soil and M. oleifera seeds used in the study were obtained from the M. oleifera community farm in Hammanskraal, Gauteng, South Africa. The clay soil was amended with plant-based organic compost purchased from the local nursery store. The amendments achieved four treatment levels namely 15 % compost / soil amendment, 30 % compost / soil amendment, 45 % compost / soil amendment and 60 % compost / soil amendment. Moringa oleifera seeds used were obtained from the same farm. Plant samples were grown in the School of Animal, Plant and Environmental Sciences (APES), University of the Witwatersrand, greenhouse under ambient temperatures. Harvesting of the leaf biomass was done after six months and nutrient analysis was carried out. Analytical techniques such as Spectroscopy and Chromatography were used for the nutrient analysis. Presence and quantity of macro and micro elements in the soil and leaves was analysed using the Inductively Coupled Plasma Optical Emission spectroscopy (ICP-OES). Whilst, the Ultra high-performance liquid chromatography coupled with electrospray ionization quadrupole time-of-flight mass spectrometry (UHPLC-ESI-QTOF-MS) was used to determine plant metabolites, and for the quantification of water-soluble vitamins by coupling it with the diode array detector (DAD). The nutrient analysis revealed that the use of organic plant-based compost for the amendment of clay soil improved the quality of the soil and M. oleifera leaves harvested from each soil amendment. The addition of the organic plant-based compost improved the macro and micro nutrients. Comparison of the different compost levels revealed that addition of plant based compost increased the bioavailability of macro and micro nutrients in the soil and increased their accumulation in M. oleifera leaves. Metabolic fingerprinting of M. oleifera leaf samples using UHPLC-ESI-QTOF-MS followed by untargeted compound analysis exposed variation in the identified metabolites. Further use of multivariate analysis in the form of PCA clustered the samples into five distinct clusters indicating diversity in the distribution of secondary metabolite as influenced by the addition of plant-based compost to the soil. The developed HPLC method was suitable for the simultaneous quantification of five B vitamins based on the low LOD and LOQ values, recovery of 97.8- 99.58% and good linearity. Application of the validated method revealed that, the addition of plant based compost significantly improved the quantity of the tested vitamins (Vitamin B1, B2, B3, B6 and B9). The 30% plant-based organic compost and clay soil combination was identified and recommended as the best compost-soil combination in improving nutrients in M. oleifera leaf biomass. It had the highest level of macro and micro nutrients. Leaves harvested from this soil/compost combination had higher concentration of Ca (45 042.5 mg/Kg), Mg (17 430 mg/Kg), P (8802. 5 mg/Kg). In addition leaves, harvested from 30% compost treatment exhibited the highest number of identified secondary metabolites and had the highest concentration of two of the five tested water soluble vitamins. This knowledge will make great contribution in the M. oleifera industry in South Africa and worldwide particularly for farmers who are into organic M. oleifera production.
A thesis submitted in fulfilment of the academic requirements for the degree of Doctor of Philosophy, to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Moringa oleifera; Organic; Plant-based compost; Minerals; Vitamins; Secondary Metabolites; UCTD; SDG-3: Good health and well-being